(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article delves into the significance of pragmatic competence in teaching speech expressions. It explores the theoretical framework, examines existing literature on the topic, and suggests methodologies for integrating pragmatic competence into language teaching. The study discusses the results of applying these methods and provides insights for future pedagogical practices in enhancing communication skills.